Leitura literária dos contos de Antônio Carlos Viana - Ferreira, Júlio Flávio Vanderlan (2020)
This work aims to build a literary reading notebook, in addition to presenting reflections on reading workshops with literary texts that were applied to a 9th grade class at a state public in the interior of Sergipe. From the application of the workshops, data were collected for reflection and preparation of the product, in this case, the pedagogical notebook. Such material was made with a reading proposal that trains readers critical of their social reality and able to appreciate the aesthetic layers of the works worked on. The texts used were the short stories “Santana Quemo-Quemo”, “Dia de parir cabrito” both present in the work Cine Privê (2009) and “Herança”, from the book O Meio do Mundo e outros contos (1999), by the Sergipe writer Antônio Carlos Viana. The vianian narratives were chosen because they deal with social problems from the perspective of their narrators who are apparently children or adolescents. The analysis of the readings took place in order to verify the trivialization of suffering arising from poverty. The themes of the works are very close to the reality of most readers. The intention was to provide a critical reception by the students, privileging the aesthetic layers of the text based on the social experiences of the readers. As a methodological basis, we use the concepts of Annie Rouxel (2014), which advocate that literary reading should be a moment of “liberation of emotions” by the reader, as well as appreciation of his “subjective memories”, in addition to Carlos Gomes (2012) that shows reading as a pedagogical practice that values the reader's social place in the process of constructing the meaning of the text. Also contributing to the text approach process, we used the theoretical contributions of the reception method by Bordini and Aguiar (1993), Cosson (2006), Eco (2011), Lima (2002), Pinheiro (2014), among other theorists who address reflective questions about teaching literature, didactics of literature, literary education and literary literacy.